Putting Indicators to Work: A Summary of Roundtable Presentations on the Latin American and Caribbean Experience with Environmental Health Indicators - Furgal, Chris (Can J Public Health, 2002)
A roundtable was held at the conclusion of the formal conference presentations to present and discuss experiences in Latin America and the Caribbean with indicator selection, implementation and use. Four presentations were given covering the following topics: the Pan American Health Organization’s (PAHO) implementation of a core indicators program in the Americas; Latin America’s use and application of the WHO developed Driving forces, Pressure, State, Exposure, Effect, Action framework (DPSEEA) for indicators; the Chilean experience in identifying, selecting and implementing indicators for use throughout the country; and finally, the use and application of the WHO DPSEEA framework to the issue of water quality monitoring in Brazil. Each paper presented a summary of knowledge gained to date from their experience and some of the strengths and challenges identified from the various approaches taken. The summary presented here provides a brief overview of the presentations given at the workshop.